2009
DOI: 10.1002/bdra.20563
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional folic acid and multivitamin supplementation for the prevention of neural tube defects and other congenital abnormalities

Abstract: The pioneering studies of Smithells et al. showed the reduction of recurrent neural-tube defects (NTD) after periconceptional folic acid-containing multivitamin supplementation. The Hungarian Periconceptional Service was established in 1984, and this primary health care system offered a chance to organize a randomized controlled trial to check whether the supplementation of a multivitamin containing 0.8 mg of folic acid during the periconceptional period is appropriate for the reduction of a first occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 61 publications
0
75
0
8
Order By: Relevance
“…59 Malnourishment overall (poor diet quality) and vitamin deficiencies (such as folic acid) are associated with various congenital malformations, including neural tube defects, congenital heart defects, and orofacial clefts. 75,76 Depressed women are also more likely to smoke, 77 and not all studies controlled for smoking despite the known association of smoking with untoward effects. 78 Although our analysis was limited to what we deemed to be above quality threshold, and metaanalysis pools data so that conclusions can be reached with higher sample sizes, the original study limitations cannot be entirely ignored.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…59 Malnourishment overall (poor diet quality) and vitamin deficiencies (such as folic acid) are associated with various congenital malformations, including neural tube defects, congenital heart defects, and orofacial clefts. 75,76 Depressed women are also more likely to smoke, 77 and not all studies controlled for smoking despite the known association of smoking with untoward effects. 78 Although our analysis was limited to what we deemed to be above quality threshold, and metaanalysis pools data so that conclusions can be reached with higher sample sizes, the original study limitations cannot be entirely ignored.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…They found a decreased frequency of atrial septal defects, no change in the frequency of other cardiac anomalies, cleft lip/palate, cleft palate, or limb defects, and an increased frequency of obstructive renal anomalies, gastroschisis, and pyloric stenosis. Finally, Czeizel 25 reported that as part of the randomized controlled trial investigating the effect of multivitamin supplementation on NTD frequency, and a subsequent cohort-controlled trial comparing outcomes in supplemented versus nonsupplemented women, it was found that urinary tract anomalies and cardiovascular defects showed a statistically significant reduction in frequency (although confidence intervals included 1 for the odds ratio of urinary tract abnormalities). The frequency of cleft lip/palate did not show a reduction in either group.…”
mentioning
confidence: 99%
“…Our hypothesis regarding the unexpected association of maternal hypotension with lower risk for total CA is based on the combination of three factors: (i) a healthier lifestyle indicated by a lower prevalence of smoking during the study pregnancy, (ii) a higher incidence of severe nausea or vomiting in pregnancy associated with a lower risk of CAs and (iii) the CA-preventive effect of folic acid and multivitamins during early pregnancy [13][14][15][16][17][18][19] in about half of the hypotensive pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, periconceptional folic acid and/or folic acid-containing multivitamin supplementation can prevent certain CAs such as neural-tube defects, [13][14][15] cardiovascular CA, urinary tract defects and congenital limb deficiencies. [16][17][18][19] Only one type of 3 mg folic acid tablet was available in Hungary during the study period. Folic acid-containing micronutrient combinations, (that is, multivitamins) had folic acid doses ranging from 0.1 to 1 mg per tablet.…”
Section: Diagnostic Criteria Of Hypotensionmentioning
confidence: 99%